Quality by Design (QbD) based development and validation of rp-hplc method for amlodipine besylate and its impurity from bulk and formulation - NANDA BADHE; ANAND SAVKARE; UJWALA BAGMAR (International Journal of Pharma and Bio Sciences, 2017)
Quality by Design (QbD) is “a systematic approach to development that begins with predefined objectives and emphasizes product and process understanding and process control, based on sound science and quality risk management” and has the aim of improving product quality and of increasing regulatory flexibility. In the pharmaceutical world, an impurity is considered as any other organic material, besides the drug substance, or ingredients arise out of synthesis or an unwanted chemical that remains with API’s. The present study describes the development of a comprehensive science and risk based RP- HPLC method and subsequent validation for the analysis of Amlodipine Besylate and its Impurity using a quality by design approach. The scheme was performed by using Hantzch pyridine synthesis. The impurity was recrystallized and preliminary evaluation was done on laboratory scale viz. Melting point, TLC and elemental analysis. The characterization of synthesized Amlodipine impurity was carried out by using sophisticated instrument such as, FT-IR, NMR, HPTLC, LC-MS, and RP-HPLC. An efficient experimental design based on systematic scouting of all three key components of the RPâ€HPLC method (pH, Flow rate and mobile phase composition) is presented. The described method was linear. (r2=0.999). The precision and robustness values were also within the prescribed limits (<1% for system precision and <2% for other parameters). The proposed method can be successfully used to determine the drug and impurity contents of marketed formulations.